Rabies and Distemper Outbreaks in Smallest Ethiopian Wolf Population - Jorgelina Marino; Claudio Sillero-Zubiri; Asefa Deressa; Eric Bedin; Alemayehu Bitewa; Fekadu Lema; Gebeyehu Rskay; Ashley Banyard; Anthony R. Fooks (Emerging Infectious Diseases, 2017)
Widespread deaths recently devastated the smallest known population of Ethiopian wolves. Of 7 carcasses found, all 3 tested were positive for rabies. Two wolves were subsequently vaccinated for rabies; 1 of these later died from canine distemper. Only 2 of a known population of 13 wolves survived.